Analysis of community perceptions of families of patients with mental disorders at Lesung Batu Community Health Center: A cross-sectional study - Yogi Permana Putra Lenarki; Ali Harokan; Chairil Zaman (Lentera Perawat, 2025)
Background Individuals with mental illness often face social stigma that not only affects them personally but also extends to their families. Public perception of families caring for persons with mental illness plays a crucial role in supporting rehabilitation efforts and social reintegration. Objective This study aimed to examine the factors associated with community perceptions toward the families of individuals with mental illness in the working area of Lesung Batu Health Center, South Sumatra, Indonesia. Methods A cross-sectional quantitative study was conducted involving 100 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using chi-square tests and multivariate logistic regression. Results The results showed that 60% of respondents had a positive perception of the families of persons with mental illness. No significant association was found with age (p = 0.83), gender (p = 1.00), or educational level (p = 0.13). However, knowledge (p = 0.00; OR = 14.14) and attitude (p = 0.00; OR = 9.3) were significantly associated with community perception. Knowledge was identified as the most dominant factor influencing public perception. Conclusion Knowledge and attitude are key determinants of community perception toward families of individuals with mental illness, while demographic factors such as age, gender, and education showed no significant impact. Community-based mental health education programs are strongly recommended to enhance knowledge, foster positive attitudes, reduce stigma, and build stronger community support for families caring for individuals with mental illness.